Implementation of Fiqh Learning on Student Small and Medium Industry (IKM) Halal Products: Implementasi Pembelajaran Fiqh Pada Produk Halal Industri Kecil Menengah (IKM) Mahasiswa - Chosinawarotin; Annisa Nurlaily (Academia Open, 2023)
The purpose of this study is to determine the Implementation of Fiqh Learning on halal products of Small and Medium Industries (IKM) students engaged in the food and beverage industry. Because currently many entrepreneurship are growing in students for the role of universities as a forum for entrepreneurship education. Halal products have their own standards and criteria, which are derived from the requirements of Islamic Sharia and Islamic Fatwas as well as Laws and Regulations on Halal Product Assurance and other laws and regulations. This cannot be separated from the knowledge of Fiqh obtained by students. Islamic Education is integrated in the Islamic Religious Education course which contains Fiqh material learning, aiming that students can recognize, understand, appreciate and practice Islamic Law as the basis of their outlook on life. The influence of Fiqh knowledge will have an impact on student behavior in producing a halal product. The method used in this study is the Qualitative method, with a Phenomenological approach. Highlights: Importance of Fiqh Knowledge: Fiqh learning plays a crucial role in guiding students to understand and adhere to the standards and criteria of halal products, based on Islamic Sharia and Fatwas, in the food and beverage industry. Integration of Islamic Education: Integration of Fiqh material into Islamic Religious Education courses ensures that students recognize, understand, and appreciate Islamic Law, providing a strong foundation for their outlook on life and business practices. Impact on Halal Product Behavior: The study aims to explore how Fiqh knowledge influences student behavior in producing halal products, leading to increased awareness and adherence to Islamic principles and regulations in their entrepreneurial ventures. Keywords: Fiqh Learning, Halal Products, Small and Medium Industries (IKM) students, Food and Beverage Industry, Entrepreneurship